Embryonic Development and Nutritional Requirements of Kutum Fry, Rutilus Frisii Kutum - Haghighi, Davoud Talebi (2006)
This study consisted of a series of experiments that were conducted to determine some biological characteristics, artificial reproduction, embryonic development, optimal level of protein and lipid in artificial diets and food regime spectrum in the stage of secondary nursing of kutum fish larvae (Rutilus frisii kutum).